Minimum needed

Algebra Level 4

x 2 + 2 x y + 3 y 2 6 x 2 y \large{x^{2}+2xy+3y^{2}-6x-2y}

For real values x , . y x,.y , find the minimum value of the expression above.


The answer is -11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Tanishq Varshney
Apr 13, 2015

Let the minimum value be m m

x 2 + 2 x y + 3 y 2 6 x 2 y m x^{2}+2xy+3y^{2}-6x-2y\geq m

x 2 + 2 x y + 3 y 2 6 x 2 y m 0 x^{2}+2xy+3y^{2}-6x-2y-m\geq 0

Its discriminant D 0 D\leq 0

4 ( y 3 ) 2 4 ( 3 y 2 2 y m ) 0 4(y-3)^{2}-4(3y^{2}-2y-m)\leq 0

2 y 2 + 4 y ( m + 9 ) 0 2y^{2}+4y-(m+9)\geq 0

y 2 + 2 y m + 9 2 y^{2}+2y\geq \frac{m+9}{2}

( y + 1 ) 2 m + 11 2 (y+1)^{2}\geq \frac{m+11}{2}

as least value of a perfect square is zero

so m + 11 2 = 0 \frac{m+11}{2}=0

m = 11 \boxed{m=-11}

Moderator note:

Why is this true?

Its discriminant D 0 D\leq 0

Discriminant is less than equal to zero because the quadratic in x is upward parabola and is nonnegative for all real values of x

Ravi Dwivedi - 5 years, 9 months ago
John Schwendinger
May 15, 2015

There is a quicker way to do this with calculus, but it is still possible with only algebra:

First off, factor with respect to x.

x 2 + 2 ( y 3 ) x + ( 3 y 2 2 y ) x^2 + 2(y - 3)x + (3y^2-2y)

Complete the square and simplify:

x 2 + 2 ( y 3 ) x + ( y 3 ) 2 ( y 3 ) 2 + ( 3 y 2 2 y ) x^2 + 2(y - 3)x + (y - 3)^2 - (y - 3)^2 + (3y^2 - 2y)

( x + ( y 3 ) ) 2 ( y 2 6 y + 9 ) + ( 3 y 2 2 y ) (x + (y - 3))^2 - (y^2 - 6y + 9) + (3y^2 - 2y)

( x + ( y 3 ) ) 2 y 2 + 6 y 9 + 3 y 2 2 y (x + (y - 3))^2 - y^2 + 6y - 9 + 3y^2 - 2y

( x + ( y 3 ) ) 2 + 2 y 2 + 4 y 9 (x + (y - 3))^2 + 2y^2 + 4y - 9

Then, complete the square with regard to the y variables, and simplify:

( x + ( y 3 ) ) 2 + 2 y 2 + 4 y 9 (x + (y - 3))^2 + 2y^2 + 4y - 9

( x + ( y 3 ) ) 2 + 2 ( y 2 + 2 y ) 9 (x + (y - 3))^2 + 2(y^2 + 2y) - 9

( x + ( y 3 ) ) 2 + 2 ( y 2 + 2 y + 1 1 ) 9 (x + (y - 3))^2 + 2(y^2 + 2y + 1 - 1) - 9

( x + ( y 3 ) ) 2 + 2 ( y 2 + 2 y + 1 ) 2 9 (x + (y - 3))^2 + 2(y^2 + 2y + 1) - 2 - 9

( x + ( y 3 ) ) 2 + 2 ( y + 1 ) 2 11 (x + (y - 3))^2 + 2(y + 1)^2 - 11

You could stop here, since the lowest value any square number can have (in real number space) is 0, the minimum value of this equation is -11. But let's solve for the variables and make sure.

The second term contains only a y y variable, so if we set y = 1 y = -1 that term is cancelled out.

This makes the first term ( x + ( 1 3 ) ) (x + (-1 - 3)) or ( x 4 ) (x - 4) so x = 4 x = 4 . And at this point, the first two terms are zero, making the minimum value -11.

Checking the values in the original equation, you get:

4 2 + 2 ( 4 ) ( 1 ) + 3 ( 1 ) 2 6 ( 4 ) 2 ( 1 ) = 16 8 + 3 24 + 2 = 11 4^2 + 2(4)(-1) + 3(-1)^2 - 6(4) - 2(-1) = 16 - 8 + 3 - 24 + 2 = -11

Moderator note:

Nicely done. Optimizing quadratic expressions via completing the square is underrated.

Partial derivatives will do the magic

1
2
3
4
5
6
take the partial derivatives with respect to x and y then set both to zero
pd w/ resp to x = 2x+2y-6 = 0
pd w/ resp to y = 2x+6y-2 = 0

x=4, y=-1
then substitue

Moderator note:

You have only shown that its local extrema occur at ( 4 , 1 ) (4,-1) but you didn't show that it is a minimum, maximum, or an inflection point.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...